(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The importance of the school canteen is highlighted by the development of nutritious foods and a desire among students to purchase a variety of foods. The Canteen can be helpful among the students when it comes to accessibility and the low budget price on the menu. It can be a problem for the students when it comes to the quality of food and the hygiene of every staff. According to the results of the surveys, many students agreed that the canteen in BSHM is in good condition in terms of the quality of food, facilities, and staff. Every area of the canteen, especially the kitchen, where all the items that the students have ordered are processed, should be kept clean by the canteen staff. For the students to be confident that the products they have ordered are completely clean and healthy, all canteen staff members should maintain consistency when it comes to proper hygiene. When it comes to the food they order, the students should pay closer attention. In order for the canteen employees to recognize the exact problem that needs to be resolved or improved, they must express their criticism of the meal that was provided to them. The Canteen Staff should maintain cleanliness in every area of the canteen, especially in the kitchen area wherein they process all the products that the students have ordered. The students should be more observant when it comes to the food that they order. Administration should be more aware of the canteen’s performance so that both parties are aware of what has to be done.